Crystal structure of 5-((bis(pyridin-2-ylmethyl)amino)methyl)quinolin-8-ol, C22H20N4O - Jia Liu; Xu-Liang Nie; Zhong-Ping Yin; Da-Yong Peng; Xu-Gen Shi (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C22H20N4O, monoclinic, P21/n (no. 14), a = 11.1861(14) Å, b = 8.1418(10) Å, c = 20.461(3) Å, β = 97.433(1)°, V = 1847.8(4) Å3, Z = 4, Rgt(F) = 0.0357, wRref(F2) = 0.1002, T = 296(2) K.